ANALISIS KUALITATIF TEKNOLOGI 5G PENGGANTI 4G DI INDONESIA - Andalisto, Ditra; Saragih, Yuliarman; Ibrahim, Ibrahim (DPTE FT UNY, 2022)
ABSTRACT:This scientific paper discusses and finds that the need for 5G in Indonesia is of a high level of urgency because it is needed by almost everyone in the use of voice calls, internet data and video as online transmissions such as distance learning, video conferencing, webinars, and election of regional leaders online. . This mass use requires a large-capacity band width and 5G is able to answer that need. However, from the results of this qualitative research, it was found that the situation of telecommunications infrastructure in Indonesia which is an archipelagic country has not been able to install 5G devices in all areas including frontier, remote, and disadvantaged (3T) areas in the near future even though the Indonesian Ministry of Communication and Informatics had announced a commercial 5G target. In 2020 but not yet proven. Meanwhile, the continuity of 4G, which has very high costs, has not yet returned the investment (Break Even Point) to operators of wireless telephone operators, so that the 5G decision for now in Indonesia cannot be implemented due to these factors.ABSTRAK:Tulisan ilmiah ini membahas dan menemukan bahwa kebutuhan 5G di Indonesia dengan tingkat urgensi yang tinggi karena dibutuhkan hampir semua orang dalam penggunaan voice call, data internet dan video sebagai transmisi daring seperti belajar jarak jauh, video conference, webinar, serta pemilihan para pemimpin daerah secara daring. Pemakaian massal tersebut membutuhkan lebar band berkapasitas besar dan 5G mampu menjawab kebutuhan itu. Namun dari hasil penelitian kualitatif ini maka ditemukan bahwa situasi infrastruktur telekomunikasi di Indonesia yang merupakan negara kepulauan belum mampu memasang perangkat 5G di seluruh area termasuk daerah terdepan, terpencil, dan tertinggal (3T) dalam waktu dekat walaupun sempat dicanangkan kementerian kominfo indonesia target komersial 5G ada di tahun 2020 tapi belum terbukti. Sementara keberlangsungan 4G yang berbiaya sangat tinggi belum balik modal (Break Even Point) kepada operator penyelenggara telepon tanpa kabel sehingga keputusan 5G untuk saat ini di Indonesia belum dapat dilaksanakan karena faktor-faktor tersebut.